Air Pollution Modeling and its Application XXIII - Steyn, Douw; Mathur, Rohit (Springer Proceedings in Complexity, 2014)
Recent developments in air pollution modelling are explored as a series of contributions from researchers at the forefront of their field. This newest contribution on air pollution modelling and its application is focused on local, urban, regional and intercontinental modelling; data assimilation and air quality forecasting; model assessment and evaluation; aerosol transformation. Additionally, this work also examines the relationship between air quality and human health and the effects of climate change on air quality. The work derives from  a series of papers presented at the 33rd International Technical Meeting on Air Pollution Modelling and its Application held in Miami, USA, August 27 - 31, 2013.  The book is intended as reference material for students and professors interested in air pollution modelling at the graduate level as well as researchers and professionals involved in developing and utilizing air pollution models.